Increase the speed of running 100 meters using the bench and skipping training methods - Muhammad Rusli; Marsuna; Jud (IP Iermakov S.S., 2024)
Background and Study Aim. Running 100 meters requires optimal speed, strength, and physical endurance. Running speed is often a key indicator of physical ability and athletic performance. However, not everyone achieves optimal speed and physical ability in running the 100 meters. Many factors influence a student's running performance, including the training methods used. The aim of the research is to determine the increase in speed for running 100 meters using bench and skipping training methods. Material and Methods. This research is an experimental study aiming to find cause and effect relationships in one or more experimental groups through different training treatments. The design used is a two-group pretest-posttest design. The participants were male students actively involved in sports activities, capable of performing running techniques well, and willing to participate in the training sessions. Initially, students underwent a pretest to determine their treatment group by ranking the pretest scores. This allowed the formation of two groups: one group of 15 students participating in bench climbing exercises, and another group of 15 students engaging in skipping exercises, using ordinal pairing. The instrument used for the 100-meter running test is the 100-meter running test. Results. Based on the results of hypothesis testing using pretest and posttest t-tests, the 100-meter running speed after bench up and down training was 4.621. The pretest and posttest data for 100-meter running speed with skipping training was 4.790. For the posttest, the running speed for 100 meters with bench up and down training and skipping training was 4.240. The two-way p-value was 0.000, which is less than 0.05, indicating a significant difference in the 100-meter running speed before and after the exercise. Conclusions. Bench climbing exercises can increase the strength of the primary leg muscles used in sprinting, such as the quadriceps, hamstrings, and calves. These exercises improve body balance and coordination, which are crucial for efficient running posture and technique. Meanwhile, skipping can enhance explosive power and the ability of leg muscles to generate power quickly and efficiently. Skipping also improves coordination between hands and feet, aiding in maintaining rhythm and efficiency in running movements. Overall, bench climbing exercises are more effective in improving 100-meter running performance compared to skipping exercises.